Collaborative governance in integrative architectural and urban planning - Lisac, Rene; Careva, Kristina; Giljević, Teo; Lalić Novak, Goranka; Vukojičić Tomić, Tijana (EAAE Annual Conference Proceedings, 2025)
This paper presents an interdisciplinary educational unit. It aims to connect contemporary knowledge on collaborative governance with knowledge on integrative architectural and urban planning. These thoughts and working methods are already on the borders of professions, and they are also interdisciplinary. They are connected through the criteria of sustainable development in the pursuit of achieving a citizen- and community-oriented and more integrated society. We believe that the related learning principle contributes to reducing misunderstandings and developing new and suitable methods for transferring good design into the built environment, by using citizen participation as a driver of intentions and a test for decisions. Students can learn how governance principles can be implemented, supported and influenced, all with the goal of making informed (evidence-based) decisions about changes in our built environment. Architecture students gain a better understanding of the functioning of the society in the context of which they attempt to design. Such insights enable them to better communicate in their professional work. Specifically, when we talk about stakeholders of the civil sector, students are introduced to particIpatory methods, in order to better integrate the needs of the community into functional, formative and constructive solutions. Special attention is paid to the possibilities and ways of involving citizens in the detection of real problems, the selection of adequate solutions and the successful use of spatial artifacts. This ultimately contributes to the development of the cooperation skills needed to adequately deal with the multiple crises the world faces today.